Front Matter Vol 1 Issue 1 January 2023 - Ridwan (Journal of Infrastructure and Construction Technology, 2023)
Statements of fact and opinion in the articles in the Journal of Infrastructure and Construction Technology are those of the respective authors and contributors and not of Journal of Infrastructure and Construction Technology. Neither Department of Civil Engineering Universitas Riau nor Journal of Infrastructure and Construction Technology make any representation, express or implied, in respect of the accuracy of the material in this journal and cannot accept any legal responsibility or liability for any errors or omissions that may be made by the reader should make her or his own evaluation as to the appropriateness or otherwise of any experimental technique described.